1999
DOI: 10.1046/j.1469-8137.1999.00460.x
|View full text |Cite
|
Sign up to set email alerts
|

Root architecture and biomass allocation of three range grasses in response to nonuniform supply of nutrients and shoot defoliation

Abstract: Predictions of root architecture have been tested using only a narrow set of environmental conditions and species. There is little information on root architecture of plants growing on semi-arid grasslands where soil nutrient heterogeneity and defoliation might impose particular restrictions on root growth. We conducted a split-root study to evaluate the effect of nonuniform nutrient supply and clipping on root architecture and biomass allocation of three range grasses found in the Intermountain West of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
60
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 35 publications
6
60
1
Order By: Relevance
“…The present experiment used contrasting, but homogeneous, soil treatments only. It has been reported for some grasses that contrasting but uniform nutrient conditions may not cause differences in the root system, whereas responses do become visible when contrasting conditions are combined into non-uniform treatments (Arredondo and Johnson 1999;Fitter and Stickland 1991). Hence, further studies are needed to test whether the present conclusion that root morphology is conservative across the elevational gradient of a salt marsh is also valid in non-uniform, patchy soil environments.…”
Section: Discussionmentioning
confidence: 45%
“…The present experiment used contrasting, but homogeneous, soil treatments only. It has been reported for some grasses that contrasting but uniform nutrient conditions may not cause differences in the root system, whereas responses do become visible when contrasting conditions are combined into non-uniform treatments (Arredondo and Johnson 1999;Fitter and Stickland 1991). Hence, further studies are needed to test whether the present conclusion that root morphology is conservative across the elevational gradient of a salt marsh is also valid in non-uniform, patchy soil environments.…”
Section: Discussionmentioning
confidence: 45%
“…For grasses, the finely branched, 'herringbone' architecture enables more efficient mobile nutrient acquisition than 'dichotomous' root systems found in species like Scots pine (Fitter 2002). Grasses also exhibit high values of specific root length (SRL), that can reach 700 m g À1 (Ryser 1996;Arredondo and Johnson 1999;Atkinson 2000;Craine et al 2001;Nicotra et al 2002), while that of tree species hardly reaches 10-15 m g À1 in the case of Scots pine (Curt et al 2005). This is achieved by constructing roots of thin diameter or low tissue density (Fitter et al 1991;Lambers and Poorter 1992;Reich et al 1998).…”
Section: Discussionmentioning
confidence: 97%
“…Maintenance of lateral root growth also contributed to a stronger feedback loop on shoot growth in signalgrass as the leaf-to-root DM ratio was greater at high P supply (a more optimal level of P supply) while shoot P concentrations remained unchanged. Arredondo and Johnson (1999) suggested that plant growth rate might increase if more C was available for shoot re-growth and if the capacity for soil nutrient acquisition was greater. In fact, maintenance of root growth and extensive root systems have been suggested to underlie edaphic adaptation of brachiariagrass genotypes (Rao et al 1996a;1996b;Miles et al 2004).…”
Section: Discussionmentioning
confidence: 99%